Preparation, Characterization and Rheological Behavior of Glutathione-Chitosan Conjugates in Aqueous Media (2019)
ABSTRACT: Glutathione-chitosan conjugates are adequate carriers for anticancer treatment due to their ability for inhibition of eux pumps, improved mucoadhesivity and insitu gelling. These conjugates were obtained via carbodiimide at different reaction times in order to get different thiolation degrees (i.e., 4.4%, 5.1% and 7.0%) and their behavior in aqueous media at a pH of 4, 5 and 6 was assessed by measurements of hydrodynamic diameter, zeta potential and rheological analyses at a pH ranging from 4 to 6. Data examination was conducted by principal component analysis (PCA) which in turn explained 73.1% of data variability. All samples showed a Newtonian flow and thiolation rendered materials with a highly pronounced temperature-dependent behavior and a gel-like structure. In turn, the phase shift angle was the most prominent rheological change especially at a pH of 5.0 and 6.0 due to the formation of disulfide bonds. The thiolation degree was the most influential factor and it was inversely related to particle charge and consistency index.